2011
DOI: 10.3168/jds.2011-4256
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-trait genomic evaluation of linear type traits using genomic and phenotypic data in US Holsteins

Abstract: Currently, the USDA uses a single-trait (ST) model with several intermediate steps to obtain genomic evaluations for US Holsteins. In this study, genomic evaluations for 18 linear type traits were obtained with a multiple-trait (MT) model using a unified single-step procedure. The phenotypic type data on up to 18 traits were available for 4,813,726 Holsteins, and single nucleotide polymorphism markers from the Illumina BovineSNP50 genotyping Beadchip (Illumina Inc., San Diego, CA) were available on 17,293 bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(139 citation statements)
references
References 11 publications
8
126
2
3
Order By: Relevance
“…It is also clear that when genomic selection is applied in a population, all traits considered by the recording systems of that population would be included in the new evaluation process and optimisation of the whole genomic evaluation for all parameters would be sometimes difficult due to their different characteristics. Difficulties arise with multiple-trait genomic analyses, although application with single-step procedures was reported in literature in other species for a large number of traits (Tsuruta et al 2011). …”
Section: Genomic Selection In Pig Populationsmentioning
confidence: 99%
“…It is also clear that when genomic selection is applied in a population, all traits considered by the recording systems of that population would be included in the new evaluation process and optimisation of the whole genomic evaluation for all parameters would be sometimes difficult due to their different characteristics. Difficulties arise with multiple-trait genomic analyses, although application with single-step procedures was reported in literature in other species for a large number of traits (Tsuruta et al 2011). …”
Section: Genomic Selection In Pig Populationsmentioning
confidence: 99%
“…Large-scale genetic evaluations with the single-step approach were run for either single trait or multiple-trait analyses (Aguilar et al, 2011b;Tsuruta et al, 2011). Computing time for genetic evaluations using genomic information took twice as long as evaluations without genomic data (Tsuruta et al, 2011), but could be reduced by 4 to 11% compared with regular genetic evaluations if custom libraries are used [I. Aguilar, I. Misztal (University of Georgia, Athens), A. Legarra (University of Georgia, Athens), and S. Tsuruta (University of Georgia, Athens), unpublished data].…”
Section: Genomic Evaluationmentioning
confidence: 99%
“…Therefore, for other traits than those analysed here, the benefit of using the predictor traits may be different. For example, differences in accuracy for various type traits, while using single-or multi-trait genomic analyses shown by Tsuruta et al (2011), were up to 9%.…”
Section: Accuracymentioning
confidence: 99%
“…For example, Aguilar et al (2011) showed an increase in accuracy of conception rate when enriching A with G and an additional substantial increase when multitrait approach was used instead of the single-trait one. Tsuruta et al (2011), who analysed linear type traits of US Holsteins, showed that, in terms of accuracy, the benefit of genomic analyses instead of pedigree was persistent across all analysed traits. Another explanation of small differences in accuracy between multi-trait pedigree and genomic scenarios is that recording own phenotypes for predictor traits on the evaluated animals gives information about the Mendelian sampling in the evaluated animals.…”
Section: Accuracymentioning
confidence: 99%